Characterization of Actinomycetes Antagonistic to Vibrio parahaemoliticus Isolated from Shrimp Pond Sediment - Chau, Ngo Thi Tuong; Thanh, Le Thi Ha; Anh, Nguyen Huu Thuan (VNU Journal of Science: Earth and Environmental Sciences, 2016)
Abstract: A new emerged lethal disease that termed EMS (Early Mortality Syndrome) or AHPNS (Acute Hepatopancreatic Necrosis Syndrome) caused by Vibrio parahaemolyticus had been added to list of shrimp diseases during last recent years. However, there are no currently available methods to treat EMS. Given this circumstance, developing an alternative strategy to control infections, especially in countries found that antibiotics are not effective against EMS as Vietnam, is urgent need. In this study, a Streptomyces sp. A8 strain isolated from shrimp pond sediments in Thừa Thiên Huế showed the high activity against V. parahaemolyticus V6 and production of extracellular enzymes to decompose organic compounds which reveals the potential to involve in mineralization and nutrient cycles in the shrimp culture ponds. The Streptomyces sp. A8 strain was only resistant to several common antibiotics as ampicillin, tetracycline and penicillin-G. Selected cultivative conditions for biomass production and antagonistic activity to V. parahaemolyticus V6 of Streptomyce s sp. A8 were 96 hours, pH 8.0, 35 o C in SCB medium with concentrations of starch, casein, NaCl, DL-α-alanine and vitamin B6 were 13%, 0.6%, 16%, 0.6% and 0.02%, respectively. When being selected fermented, a large amount of Streptomyces sp. A8 biomass (15.0 g/L) was harvested. Keywords : Actinomycetes, Streptomyces sp. A8, shrimp ponds, Vibrio parahaemolyticus , early mortality syndrome.